Recognize The Fierce Competition in The Fast Fashion Industry - Anpel Rizaldy; Supiansyah Supiansyah (Universitas Prasetiya Mulya, 2023)
Inditex, Fast Retailing Co. Ltd, Gap Inc, Hennes & Mauritz AB, and Urban Outfitters Inc are world-famous industries that make fashion brand that adopts the fast fashion industry system. This article will discuss market competition in the fast fashion industry using Porter's five forces model. The analysis was carried out using descriptive qualitative methods on five samples of the fast fashion industry within a competitive market, E.g., Inditex (ZARA), Fast Retailing Co. Ltd (UNIQLO), Gap Inc (GAP), Hennes & Mauritz AB (H&M), and Urban Outfitters Inc (Urban Outfitters). That way, we will understand how difficult the competition is in the fast fashion industry environment and where able to use the analytical approach to measure competition analysis for other industries